(untitled) (Journal of Organizational Psychology, 2020)
Helping others is viewed positively and is rarely questioned. Nevertheless, attempts to aid others frequently come with actual (but often hidden, long-term) results that worsen the situations we intended to alleviate. When individuals receive benefits not based upon performance or effort and work, damaging effects often occur. As a result, some argue that people who get something for nothing become “good for nothing” and generates feelings of entitlement, laziness, and dependency. In this paper, the authors cite examples where this seems to be happening and offer recommendations for a more thoughtful approach to giving and assisting others.